2021
DOI: 10.1200/jco.2021.39.15_suppl.e12511
|View full text |Cite
|
Sign up to set email alerts
|

Application of RSClin to guide treatment recommendations for premenopausal patients with early-stage hormone-positive breast cancer and intermediate risk oncotype recurrence scores.

Abstract: e12511 Background: The RSClin model, which incorporates the Oncotype Recurrence Score (RS) and clinicopathologic features, was recently developed to further tailor prognosis and prediction of chemotherapy benefit for patients with early-stage hormone positive (HR+) breast cancer (BC) (Sparano et al, 2020). The RSClin calculator is available online to assist treatment planning for situations where chemotherapy benefit is uncertain. Covariates include Oncotype RS, tumor grade, tumor size and patient age. The ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Statistical analysis was performed with Python version 3.8.8 (Python Software Foundation, Wilmington, Delaware). Early studies of breast cancer chemotherapy demonstrated benefits of as low as 2%–3% in postmenopausal women, 19 whereas clinicians may prefer to recommend chemotherapy for patients when the benefit is >5% 9,20 . Thus, we evaluated subgroups where RSClin‐predicted chemotherapy benefit was <3% (low benefit), 3%–5% (intermediate benefit), and >5% (high benefit).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analysis was performed with Python version 3.8.8 (Python Software Foundation, Wilmington, Delaware). Early studies of breast cancer chemotherapy demonstrated benefits of as low as 2%–3% in postmenopausal women, 19 whereas clinicians may prefer to recommend chemotherapy for patients when the benefit is >5% 9,20 . Thus, we evaluated subgroups where RSClin‐predicted chemotherapy benefit was <3% (low benefit), 3%–5% (intermediate benefit), and >5% (high benefit).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reserved chemotherapy for patients where RSClin predicts at least a 5% absolute reduction in distant recurrence with the use of chemotherapy, but additional data are needed. 9 Although genomic recurrence assays have improved the care of women with HRþ breast cancer via the more appropriate selection of patients for chemotherapy, accumulating evidence suggests that these assays are less applicable to non-White patients. This may in part be due to the fact that the most well-studied genomic recurrence assays were developed with samples from predominantly White patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation